2014
DOI: 10.1007/s00247-014-2908-1
|View full text |Cite|
|
Sign up to set email alerts
|

Benefits and unexpected artifacts of biplanar digital slot-scanning imaging in children

Abstract: Biplanar digital slot-scanning allows for relatively low-dose orthopedic imaging, an advantage in imaging children given the growing concerns regarding radiosensitivity. We have used this system for approximately 1 year for orthopedic imaging of the spine and lower extremities. We have noted advantages of using the digital slot-scanning system when compared with computed radiographic and standard digital radiographic imaging systems, but we also found unexpected but common imaging artifacts that are the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…Compared with standard digital radiography, EOS examinations generally require less time and labor of the radiology technologists [35,36]. Dietrich et al [35] showed statistically significant reductions in examination times, with biplanar radiography requiring only 248 seconds to complete versus 449 seconds for standard digital radiography.…”
Section: Workflow and Efficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with standard digital radiography, EOS examinations generally require less time and labor of the radiology technologists [35,36]. Dietrich et al [35] showed statistically significant reductions in examination times, with biplanar radiography requiring only 248 seconds to complete versus 449 seconds for standard digital radiography.…”
Section: Workflow and Efficiencymentioning
confidence: 99%
“…These include patient motion artifacts, edge enhancement, potential underestimation of leg-length discrepancy, and the "off-center" artifact [36].…”
Section: Artifactsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies documented an estimated cumulative radiation exposure of 15 mSv due to periodic radiographic follow-ups, leading to notably increased cancer risk in AIS patients [26] , [27] . With the use of microdose EOS, a 58% dose reduction with the effective dose reduced from 233 mSv to 98.7 mSv could be achieved [28] , [29] . Another study also confirmed a 6- to 9-fold of average skin dose reduction in the thoracoabdominal region, with the use of slot-scanning imaging instead of CR [19] .…”
Section: Discussionmentioning
confidence: 99%